Examining eWOM Credibility - Consumer Purchase Intention Relationship in Facebook: A Mediation Analysis - Rao, Kunja Sambashiva; Rao, Bramhani (Indian Journal of Marketing, 2019)
The objective of the current study was to examine the influence of electronic word-of-mouth (eWOM) credibility on consumers' purchase intention with trust in seller and brand image as mediators. The proposed model was tested in the context of brand fan pages of Amazon on Facebook. The data were obtained from 393 customers present on Facebook fan pages of Amazon. The data were analyzed using structural equation modeling (SEM), which indicated a positive relationship between eWOM and purchase intentions. Both trust in seller and brand image partially mediated this relationship. While the study contributes to the theories of eWOM, trust, and consumer behaviour, its findings have significant implications for managers of e-commerce websites who may seek empirical evidence while developing new methods of disseminating product information through SNSs.